Association of Traditional Cardiovascular Risk Factors with Venous Thromboembolism: An Individual Participant Data Meta-analysis of Prospective Studies - Mahmoodi, Bakhtawar K.; Cushman, Mary; Næss, Inger Anne; Allison, Matthew A.; Bos, Willem Jan; Brækkan, Sigrid K.; Cannegieter, Suzanne C.; Gansevoort, Ron T.; Gona, Philimon N.; Hammerstrøm, Jens; Hansen, John-Bjarne; Heckbert, Susan; et al. (Circulation (New York, N.Y.), 2017)
BACKGROUND—There is much controversy surrounding the association of traditional cardiovascular disease (CVD) risk factors with venous thromboembolism (VTE). METHODS—We performed an individual level random-effect meta-analysis including 9 prospective studies with measured baseline CVD risk factors and validated VTE events. Definitions were harmonized across studies. Traditional CVD risk factors were modeled categorically, as well as continuously using restricted cubic splines. Estimates were obtained for overall VTE, provoked (i.e., VTE occurring in the presence of one or more established VTE risk factors) and unprovoked VTE, pulmonary embolism (PE) and deep-vein thrombosis (DVT). RESULTS—The studies included 244,865 participants with 4,910 VTE events occurring during a mean follow-up 4.7−19.7 years per study. Age, sex, and body-mass index adjusted hazard ratios for overall VTE were 0.98 (95%CI, 0.89−1.07) for hypertension, 0.97 (0.88−1.08) for hyperlipidemia, 1.01 (0.89−1.15) for diabetes and 1.19 (1.08−1.32) for current smoking. After full adjustment these estimates were numerically similar. When modeled continuously, an inverse association was observed for systolic blood pressure (HR=0.79 [95% CI, 0.68−0.92] at systolic blood pressure 160 vs. 110 mmHg), but not for diastolic blood pressure or lipid measures with VTE. An important finding from VTE subtype analyses was that cigarette smoking was associated with provoked but not with unprovoked VTE. Fully adjusted hazard ratios for the associations of current smoking with provoked and unprovoked VTE were 1.36 (95% CI, 1.22−1.52) and 1.08 (0.90−1.29), respectively. CONCLUSIONS—Except the association of cigarette smoking with provoked VTE, which is potentially mediated through comorbid conditions such as cancer, the modifiable traditional CVD risk factors are not associated with increased VTE risk. Higher systolic blood pressure showed inverse association with VTE.